Subjectivity and Humanism as Two Major Factors of Jaun Paul Sartre’s Existentialism in: Gabriel Garcia Marquez’s ‘No One Writes to the Colonel’ - Harati, Maryam; Abadi, Mohammad Mahdi Kashani Lotf (Mediterranean Journal of Social Sciences, 2011)
Existentialism, as the forerunner of twentieth centuryâ€™s thought schools, encompasses and gives far more meaning to theclassical work of literature even the most recent ones as Gabriel Garcia Marquez. It is one of the broad schools of thought and philosophythat deeply indebted to the ideas and studies of a French philosopher called Jean-Paul Sartre. â€œThe more fashionable a philosophybecomesâ€, Marjorie Grene states in his Introduction to Existentialism, â€œthe more elusive is its definitionâ€ (Grene 23). So, the proponentsof existentialism proclaim that though many attacks few understand them" (Elizabeth 1). Regarding the school of existentialism and theMarquezâ€™s work called No One Writes to the Colonel; this study concentrates on Subjectivity and humanism as viewed in this novel andas applied from the school. Sartre's existential elements, such as Subjectivity and Freedom, to choose as the two basic issues ofexistentialism, are applicable and seen through this novel. The major character of the novel, a Colonel, makes his mind up to choosewaiting and through this decision, he gave meaning to his life and his own subjectivity. Finally the study comes to the conclusion that theColonel of Marquezâ€™s novel â€“No One Writes to the Colonel- is an Existential human being, since he decides, accepts the responsibilities,alienates himself, and becomes a sort of stranger in his hometown. And yet, he does not lose his hope, as far as he is free, liberated tochoose for humanism. Therefore, through the challenges he gains his true subjectivity and humanism.